Utilization Of Modified SERVQUAL Model in Crafting Strategies Among Courier Services - Mendoza, Xavier Lawrence D.; Pichay, Sherina B.; Tadeo, Jerico B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Pandemic has a big impact on the whole economy especially on the business industry, most of the businesses are forcibly closed down due to the pandemic, and due to the safety measurements of the government, and businesses such as courier services are playing a vital role in building the gap between the customers and businesses. Hence, the study aimed to determine the customers’ evaluation on service quality of courier services in Tanza, Cavite. The researchers used a descriptive-correlational research design in this study. The result of the study depicted that majority of the courier service customer were female with 78.89% and age ranging from 21 to 30 years old. The majority of the participants were single. Also, College undergraduates obtained the highest percentage with 58.90%, as well as the net monthly income of the participants ranging less than Php 10,957.00. However, in terms of the customers’ level of satisfaction on the five dimensions of service quality, credibility got the highest grand mean which indicates that it is the factor that highly influences customer satisfaction. The overall satisfaction level of the participants showed that they were satisfied with the services of courier service providers. The researchers concluded that majority of courier service customers are female’s ages ranging from 21 to 30 years old. The researchers revealed that most of the courier service customers are college undergraduates and earning less than Php 10,957.00 per month. The researchers recommended strategies to courier services to improve their service quality.